Investigation of (Fe, Co)NbB-Based Nanocrystalline Soft Magnetic Alloys by Lorentz Microscopy and Off-Axis Electron Holography. (18th November 2014) - Zheng, Changlin; Kirmse, Holm; Long, Jianguo; Laughlin, David E.; McHenry, Michael E.; Neumann, Wolfgang
Abstract: The relationship between microstructure and magnetic properties of a (Fe, Co)NbB-based nanocrystalline soft magnetic alloy was investigated by analytical transmission electron microscopy (TEM). The microstructures of (Fe0.5 Co0.5 )80 Nb4 B13 Ge2 Cu1 nanocrystalline alloys annealed at different temperatures were characterized by TEM and electron diffraction. The magnetic structures were analyzed by Lorentz microscopy and off-axis electron holography, including quantitative measurement of domain wall width, induction, and in situ magnetic domain imaging. The results indicate that the magnetic domain structure and particularly the dynamical magnetization behavior of the alloys strongly depend on the microstructure of the nanocrystalline alloys. Smaller grain size and random orientation of the fine particles decrease the magneto-crystalline anisotropy and suggests better soft magnetic properties which may be explained by the anisotropy model of Herzer.